Lack of M4 muscarinic receptors in the striatum, thalamus and intergeniculate leaflet alters the biological rhythm of locomotor activity in mice - Riljak, Vladimir; Janisova, Katerina; Myslivecek, Jaromir (Brain structure & function, 2020)
The deletion of M4 muscarinic receptors (MRs) changes biological rhythm parameters in females. Here, we searched for the mechanisms responsible for these changes. We performed biological rhythm analysis in two experiments: in experiment 1, the mice [C57Bl/6NTac (WT) and M4 MR -/- mice (KO)] were first exposed to a standard LD regime (12/12-h light/dark cycle) for 8 days and then subsequently exposed to constant darkness (for 24 h/day, DD regime) for another 16 days. In experiment 2, the mice (after the standard LD regime) were exposed to the DD regime and to one light pulse (zeitgeber time 14) on day 9. We also detected M1 MRs in brain areas implicated in locomotor biological rhythm regulation. In experiment 1, the biological rhythm activity curves differed: the period (τ, duration of diurnal cycle) was shorter in the DD regime. Moreover, the day mean, mesor (midline value), night mean and their difference were higher in KO animals. The time in which the maximal slope occurred was lower in the DD regime than in the LD regime in both WT and KO but was lower in KO than in WT mice. In experiment 2, there were no differences in biological rhythm parameters between WT and KO mice. The densities of M1 MRs in the majority of areas implicated in locomotor biological rhythm were low. A significant amount of M1 MR was found in the striatum. These results suggest that although core clock output is changed by M4 MR deletion, the structures involved in biological rhythm regulation in WT and KO animals are likely the same, and the most important areas are the striatum, thalamus and intergeniculate leaflet.
Keywords: Locomotor activity; M4 muscarinic receptors; lokomoce; aktigrafie; Thalamus; receptor muskarinový M4; Actigraphy; Female; zvířata; Neostriatum; myši inbrední C57BL; Intergeniculate leaflet; Periodicity; myši knockoutované; periodicita; thalamus; Receptor, Muscarinic M4; ženské pohlaví; neostriatum; Mice, Knockout; Mice, Inbred C57BL; M1 muscarinic receptors; Locomotion; Animals; Biorhythm